PERAN ZAKAT SEBAGAI PENDORONG MULTIPLIER EKONOMI - Muhammad Nasrullah (Jurnal Hukum Islam, 2010)
The number of poor moslem people always increase. Education and income gaps are regarded as cause of the poor getting poorer and the rich get richer. It is the responsibility for Muslims to help each other to alleviate poverty through performing and empowering the zakat. Zakat plays an important role in the economy, especially in reducing poverty. The existence of zakat will increase aggregate demands from mustahiq raise; then it will increase aggregate supply and employment. This is known as an economic multiplier. The well managed zakat will bring about the great benefit of zakat in economy, especially to overcome the destituiton.